[Stream Through Landmannalaugar] - Streng, Evelyn Fiedler (1975)
Photograph of a stream through Landmannalaugar. The flat plain surrounded by grass covered, brown mountains is broken up by a large, light blue stream sits along the left edge of the photograph. Black, rocky platforms sits between the mountains along the flat, central plain.